The aporias of kitsch - Radojičić, Mirjana (Array, 2019)
The text is based on the standpoint that the indeterminateness of the term of kitsch understood as pseudo-art feeds upon the indeterminateness of art as its correlate term. However, as the author perceives, that does not reduce the theoretical efforts aimed at establishing, on this slippery and unsafe “field”, some firmer demarcation lines, some more reliable discrimen rerum between those categories, which are, at least on the phenomenal plane, very close to each other. This paper attempts to do that by viewing kitsch from the angle of the aesthetics of reception, then from the angle of the sociology of art and, finally, from the axiological point of view.